2022
DOI: 10.15252/embj.2022110698
|View full text |Cite
|
Sign up to set email alerts
|

Defining the proximal interaction networks of Arf GTPases reveals a mechanism for the regulation of PLD1 and PI4KB

Abstract: The Arf GTPase family is involved in a wide range of cellular regulation including membrane trafficking and organelle–structure assembly. Here, we have generated a proximity interaction network for the Arf family using the miniTurboID approach combined with TMT‐based quantitative mass spectrometry. Our interactome confirmed known interactions and identified many novel interactors that provide leads for defining Arf pathway cell biological functions. We explored the unexpected finding that phospholipase D1 (PLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 84 publications
3
23
0
Order By: Relevance
“…S1, B and C ). In agreement with our results that both RUFY1 and RUFY3 interact with Arl8b, a recent study has identified both proteins as significant hits in the proximal interaction network of Arl8a and Arl8b ( Li et al, 2022 ).…”
Section: Resultssupporting
confidence: 93%
“…S1, B and C ). In agreement with our results that both RUFY1 and RUFY3 interact with Arl8b, a recent study has identified both proteins as significant hits in the proximal interaction network of Arl8a and Arl8b ( Li et al, 2022 ).…”
Section: Resultssupporting
confidence: 93%
“…PLD1 is a somewhat enigmatic phospholipase that hydrolyses PC to form PA, with various poorly defined roles in signal transduction, endocytosis, exocytosis and membrane trafficking (McDermott et al , 2020). Previous work has indicated that Arf1/6 can regulate PLD1 but, somewhat counter‐intuitively, Li et al (2022) now clearly show that ARL11/14 binds to a distinct region of this protein (the so‐called “loop region”) in a GTP‐dependent manner, causing an impressive activation of PLD activity. Further, knock‐out of ARL11 reduces phagocytosis of zymosan particles in a macrophage‐like cell line, and knock‐out of PLD1 prevents the ability of heterologously expressed ARL11 Q67L (a GTPase defective mutant) to stimulate phagocytosis in the same cell line.…”
Section: Figure Proximity Labelling Reveals Novel Roles Of Arf Family...mentioning
confidence: 98%
“…Proximity labelling was applied by Li et al (2022) to screen the proximal interactors of 25 members of the Arf family of small GTPases. Constitutively active mutants of each GTPase were fused to miniTurbo biotin ligase and stably expressed in HEK293 cells.…”
Section: Figure Proximity Labelling Reveals Novel Roles Of Arf Family...mentioning
confidence: 99%
See 2 more Smart Citations